PENINGKATAN PENGETAHUAN TENTANG SEJARAH BAGI SISWA SMP NEGERI 2 KELAPA DUA TANGERANG MELALUI WISATA EDUKASI - KRISTIANA, YUSTISIA (Buletin Udayana Mengabdi; Vol 14 No 1 (2015): April 2015)
Edutourism is a program combining elements of tourist activities with education. Edutourism is expected to be a means of preserving the culture values and introduce the history and culture of Indonesia. This is because the phenomena among the younger generation who are no longer interested in studying history. Sekolah Tinggi Pariwisata Pelita Harapan, Universitas Pelita Harapan developed educational travel programs catering for students of junior high schools to enhance interest in learning history. Students of SMP Negeri 2 Kelapa Dua Tangerang were selected to attend this edutourism program by visiting Monumen Nasional and Museum Sejarah Jakarta. This program was conducted on Tuesday, April 17th, 2012 with total participants were 20 students and two teachers. Edutourism program was led by lecturer and guided by students of Travel Industry Management. The students and the team from Travel Industry Management were very enthusiastic during the edutourism. Benefits obtained by the students through this program are (1) improving the understanding about historical sites in Jakarta, (2) widening the knowledge about historical sites in Jakarta, and (3) developing the partnership between the SMP Negeri 2 Kelapa Dua Tangerang and Sekolah Tinggi Pariwisata Pelita Harapan, Universitas Pelita Harapan. The edutourism program is well accepted and effective to increase student’s interest in learning history. Keywords: edutourism, student’s interest in learning history, historical site